2006
DOI: 10.1038/sj.hdy.6800846
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination and inbreeding depression in an ant with regular sib-mating

Abstract: Haplodiploidy is one of the most widespread mechanisms of sex determination in animals. In many Hymenoptera, including all hitherto investigated social species, diploid individuals, which are heterozygous at the sex locus, develop as females, whereas haploid, hemizygous individuals develop as males (single-locus complementary sex determination, sl-CSD). Inbreeding leads to homozygosity at the sex locus, resulting in the production of diploid males, which are usually sterile and constitute a considerable fitnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 38 publications
0
55
3
Order By: Relevance
“…Several studies suggested their results might be better explained by ml-CSD rather than sl-CSD (Garofolo 1973;Kerr 1974;Naito et al 2000), while others found no support for ml-CSD in a range of other species (Skinner and Werren 1980;Cook 1993a;Periquet et al 1993;Butcher et al 2000;Niyibigira et al 2004a;Schrempf et al 2006). Here, we show that inbreeding the braconid wasp C. vestalis for eight generations results in increasing proportions of DM and an increasingly male-biased sex ratio (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggested their results might be better explained by ml-CSD rather than sl-CSD (Garofolo 1973;Kerr 1974;Naito et al 2000), while others found no support for ml-CSD in a range of other species (Skinner and Werren 1980;Cook 1993a;Periquet et al 1993;Butcher et al 2000;Niyibigira et al 2004a;Schrempf et al 2006). Here, we show that inbreeding the braconid wasp C. vestalis for eight generations results in increasing proportions of DM and an increasingly male-biased sex ratio (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…A similar diversity of sex determining systems can be found more broadly in the Braconidae as well (Beukeboom et al 2000;Wu et al 2005;van Wilgenburg et al 2006). Another interesting group is the ant family, Formicidae, because many species are believed to have sl-CSD (van Wilgenburg et al 2006), but it appears to be absent in the inbreeding ant Cardiocondyla batesii (Schrempf et al 2006). Also, a number of socially parasitic ants engage in inbreeding, bringing into question whether they have sl-CSD (Crozier and Pamilo 1996).…”
Section: Discussionmentioning
confidence: 99%
“…First, genetic mechanisms may prevent homozygosity at the CSD loci, such as multiple-loci complementary sex determination (ml-CSD) (Crozier, 1971) or genomic imprinting (Beukeboom, 1995). To date, ml-CSD has not been directly shown in a social Hymenoptera, but good evidence against single-locus complementary sex determination has recently been published for Cardiocondyla elegans (Schrempf et al, 2006). Genomic imprinting cannot be tested without appropriate cytogenetic markers, such as the paternal sex-ratio chromosome (PSR) in Nasonia vitripennis (Dobson and Tanouye, 1998;Beukeboom and Werren, 2000), which are not available for any ant species.…”
Section: Discussionmentioning
confidence: 99%
“…Both authors showed that haplodiploids without complementary sex determination experience substantial inbreeding depression, although lower than that experienced by diploids. Furthermore, even some haplodiploid species with systematically-inbreeding mating systems still experience inbreeding depression (Luna and Hawkins, 2004;Schremph et al, 2006). These results indicate that haplodiploidy does not offer complete immunity from inbreeding depression, and that both overdominance and dominance in female-limited genes likely constitute a significant source of inbreeding depression in haplodiploids.…”
Section: Haplodiploidy Inbreeding Depression and Bee Declinesmentioning
confidence: 77%